Experiencing work experience[Sound recording] (Video Education Australasia, 1996)
This program aims to assist in preparing year 10 & 11 students for their school based work experience program. It provides useful information on what work experience can be like and the benefits it can yield. Employers and career teachers provide tips on the "do's" and "dont's" when undertaking work experience